Homesickness among International Students in Famagusta, North Cyprus - Oghenerhoro, Akpotor Abigail (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The study’s aim was to examine the issue of homesickness among international students studying in North Cyprus and to educate the entire world especially incoming or new international students on homesickness. These 4 objectives were set to achieve this aims: 1.To establish whether the international students studying in North Cyprus were homesick or not. 2.To determine the reasons for international students’ homesickness. 3.To examine the impacts of homesickness on international students; health, academic performance, behavior and character. 4. To understand how international students deal or cope with homesickness. In order to collect data a qualitative approach to research was adopted, through semi structured interviews; 29 African students who suffered from homesickness were interviewed. The data analysed shows that these international students missed several aspects of their homes like: family, friends, food and many more. Language barrier was identified as one of the main causes of homesickness, it also deprieved international students the opportunity of becoming friends with their fellow students and locals in the community. In some cases language barrier caused problems due to misunderstandings and lack of communication. Keywords: Homesickness, international students, African students, North Cyprus.

ÖZ: Çalışmanın amacı, Kuzey Kıbrıs'ta okuyan uluslararası öğrenciler arasında ev hastalığı konusunu incelemek ve tüm dünyayı özellikle gelen veya yeni uluslararası öğrencileri ev hastalığı konusunda eğitmekti. Bu 4 hedef bu hedeflere ulaşmak için belirlenmiştir: 1.Kıbrıs'ta eğitim gören uluslararası öğrencilerin evde hasta olup olmadıklarını belirlemek. 2.Uluslararası öğrencilerin ev hastalıklarının nedenlerini belirlemek. 3.Evde hastalığın uluslararası öğrenciler üzerindeki etkilerini incelemek; sağlık, akademik performans, davranış ve karakter. 4. Uluslararası öğrencilerin ev hastalıklarıyla nasıl başa çıktıklarını veya başa çıkmalarını anlamak. Veri toplamak için yarı yapılandırılmış görüşmeler yoluyla araştırmaya nitel bir yaklaşım benimsenmiştir; Evde hastalıktan muzdarip 29 Afrikalı öğrenci ile görüşme yapılmıştır. Analiz edilen veriler, bu uluslararası öğrencilerin evlerinin aile, arkadaşlar, yiyecekler ve daha pek çok yönünü kaçırdığını göstermektedir. Dil engeli, ev hastalıklarının ana nedenlerinden biri olarak tanımlandı, aynı zamanda uluslararası öğrencilere, toplumdaki diğer öğrenciler ve yerlilerle arkadaş olma fırsatını da mahrum etti. Bazı durumlarda dil engeli yanlış anlaşılmalar ve iletişim eksikliği nedeniyle sorunlara neden oldu. Anahtar Kelimeler: Ev hastalığı, uluslararası öğrenciler, Afrikalı öğrenciler, Kuzey Kıbrıs.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2020. Supervisor: Assist. Prof. Dr. İlkay Yorgancı Maloney.
Keywords: Tourism; Students--Homesickness--Famagusta (Cyprus, North); University Students--International Students--Mental Health; Homesickness; international students; African students; North Cyprus